The Effect Of Compensation and Work Environment On Employee Job Satisfaction with Organizational Commitment as an Intervening Variable at the Bank Indonesia Pematang Siantar Representative Office - Gomgom S. G. Sirait; M. Isa Indrawan; Kiki Farida Ferine (CV. Doki Course and Training, 2026)
This study aims to analyze how compensation and work environment influence employee job satisfaction, with organizational commitment acting as a mediating factor at the Bank Indonesia Representative Office in Pematangsiantar. A quantitative method was employed, employing Structural Equation Modeling (SEM) analysis using SmartPLS 3.0 software. The sample for this study consisted of all employees at the Bank Indonesia Representative Office in Pematangsiantar, selected through purposive sampling. The results indicate that organizational commitment has a positive and significant impact on employee job satisfaction, while compensation does not have a significant direct effect on job satisfaction. Furthermore, both compensation and work environment exhibit positive and significant impacts on organizational commitment. The work environment also has a positive and significant impact on employee job satisfaction. However, organizational commitment does not effectively mediate the relationship between compensation or work environment and job satisfaction. Considering these findings, it is recommended that management focus on enhancing organizational commitment and fostering a pleasant and supportive work environment to enhance employee job satisfaction, while providing fair compensation to strengthen employee bonds with the organization.